2015
DOI: 10.1177/0022022115605384
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interdependent and Independent Priming on Western Participants’ Ability to Perceive Changes in Visual Scenes

Abstract: The current study examined whether priming interdependent relative to independent selfknowledge would induce different thinking styles among Western participants, and whether this would, in turn, affect the speed of detecting changes in a change-blindness task. Based on predictions from the semantic-procedural interface model, we predicted that participants would attend more to the context following an interdependent self-construal priming manipulation than following an independent self-construal priming manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
(55 reference statements)
0
24
1
Order By: Relevance
“…These predictions have been supported by many experimental studies that have used self- construal priming techniques (e.g., Choi, Connor, Wason, & Kahan, 2016 ; Haberstroh et al, 2002 ; Kühnen & Oyserman, 2002 ). These effects have been very well summarized by Oyserman and Lee (2008) in a meta-analytic review of the cultural priming literature.…”
Section: Effects Of Cultural Mindset Priming On Cognitionmentioning
confidence: 63%
See 3 more Smart Citations
“…These predictions have been supported by many experimental studies that have used self- construal priming techniques (e.g., Choi, Connor, Wason, & Kahan, 2016 ; Haberstroh et al, 2002 ; Kühnen & Oyserman, 2002 ). These effects have been very well summarized by Oyserman and Lee (2008) in a meta-analytic review of the cultural priming literature.…”
Section: Effects Of Cultural Mindset Priming On Cognitionmentioning
confidence: 63%
“…Prior research has shown that activation of an interdependent self-construal induces context dependent information processing, i.e. the tendency to process stimuli while paying attention to their relations to the entire field ( Choi, Connor, Wason, & Kahan, 2016 ; Kühnen, Hannover, & Schubert, 2001 ; Kühnen & Oyserman, 2002 ). The present study extends this phenomenon to the organizational context by demonstrating that increasing accessibility to a context dependent thinking style increases raters’ sensitivity to contextual behaviors and most likely that is why they tend to place higher weights on OCBs when making overall performance judgments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulative research also suggests that self-construal impacts human perception and cognition in a various ways, including for example, relational and well-being assessment (Cross & Morris, 2003), changes in visual scenes (Choi, Connor, Wason, & Kahan, 2016), organizational events (Pekerti & Kwantes, 2011), and opinion formation (e.g., Ybarra & Trafimow, 1998) in which the use of a subjective heuristic (e.g., the majority rule) may be involved. Selfconstrual refers to views of self and how a person defines the self in relation to others.…”
Section: Introductionmentioning
confidence: 99%